Econometric Modelling of Lithuanian Labour Market - Tendziagolskytė, Dalia; Rudzkis, Rimantas (Lithuanian Journal of Statistics, 2014)
Lithuanian labour market indicators, such as the total number of employees, the number of employees in the private and public sectors, the number of the unemployed, labour force, employment and unemployment rates, the relative number of employees, average monthly gross income are analysed in the paper. The experience of foreign countries and Lithuania in creating labour market models and econometric methodology has been examined. As a result, a new model of the Lithuanian labour market is produced, comprising ﬁve regressive equations, which are part of the recursive SVAR model, and four identities, which are part of balance equations. According to the logic of economic and other research, relevant connections in the economy have been specified, unknown parameters of equations have been estimated. Finally, forecasts of endogenous indicators for 2014 have been provided, and results have been compared with the projections of the main labour market indicators for 2014−2017, published by the Ministry of Finance. Calculations have been made using a statistical package Gretl.